Individual Emotions, Academic Competence and Self-perceptions under Family Influence: A Case Study of Non-Key Secondary Schools in County Areas of China - Song, Ziyi (Transactions on Social Science, Education and Humanities Research, 2024)
This study explored the effects of family environment on students’ emotions, academic abilities and self-perceptions in a non-key secondary school in a Chinese county. A sample of 44 students in a senior class of a county non-key secondary school in Shandong Province was selected to systematically analyse the relationship between family factors and students’ emotional stability, academic performance and self-perception, as well as the correlations between the factors, through questionnaires and field observations. It was found that family financial support and amicable atmosphere had a positive impact on academic performance, while parental marital conflict had a negative impact. In addition, students’ emotional states, self-perceptions, and conceptions of marriage were all affected by the family environment to varying degrees. Factors such as family economic conditions, family relationships, and parental marital status collectively contribute to students’ personality, academic stability, and emotional management. This study enriches the theories of family pedagogy and emotional psychology, provides practical guidance for educators and parents, and has practical significance and practical value for the educational reform of non-focused secondary schools in county areas of China.